Why monarchy persists in small states: the cases of Tonga, Bhutan and Liechtenstein. Issue 4 (7th June 2017) - Corbett, Jack; Veenendaal, Wouter; Ugyel, Lhawang
ABSTRACT: Monarchical rule is said to have become anachronistic in a modern age of legal rational orders and representative institutions. And yet, despite successive waves of democratization having usurped their authority across much of the globe, a select few monarchs remain defiant, especially in small states. This stubborn persistence raises questions about the application of Huntington's "King's Dilemma" in which modern monarchs are apparently trapped in a historical cycle that will ultimately strip them of meaningful power. Drawing on in-depth historical research in three small states that have sought to combine democratic and monarchical rule – Tonga, Bhutan, and Liechtenstein – we argue that, contra Huntington, monarchs in small states are neither doomed to disappear nor are they likely to be overwhelmed by the dilemma posed by modernist development. The lesson is that the size of political units is a critical variable too often overlooked in existing studies.